1998
DOI: 10.1021/je980149e
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Anthracene in Ternary Propanol + 2,2,4-Trimethylpentane + Cyclohexane and Butanol + 2,2,4-Trimethylpentane + Cyclohexane Solvent Mixtures

Abstract: Experimental solubilities are reported for anthracene dissolved in ternary 1-propanol + 2,2,4-trimethylpentane + cyclohexane, 2-propanol + 2,2,4-trimethylpentane + cyclohexane, 1-butanol + 2,2,4-trimethylpentane + cyclohexane, and 2-butanol + 2,2,4-trimethylpentane + cyclohexane solvent mixtures at 25°C. Nineteen compositions were studied for each of the four solvent systems. Results of these measurements are used to test the predictive ability of the ternary solvent form of the combined NIMS/ Redlich-Kister e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 7 publications
0
39
4
Order By: Relevance
“…In the case of structurally similar drug molecules the numerical values of the S i coefficients were found to be nearly constant in a given binary solvent mixture. 10 For a ternary solvent system, the mathematical representation takes the form of Recent studies have shown that eq 3 provides reasonably accurate predictions for anthracene solubilities in ternary two alkane + alcohol 14,15 and alkane + two alcohol [16][17][18] solvent mixtures. Such systems exhibit fairly large deviations from solution ideality arising from the self-association of each alcohol cosolvent and, in mixtures containing two alcohol cosolvents, from the formation of heterogeneous hydrogen-bonded chains between dissimilar alcohol molecules.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of structurally similar drug molecules the numerical values of the S i coefficients were found to be nearly constant in a given binary solvent mixture. 10 For a ternary solvent system, the mathematical representation takes the form of Recent studies have shown that eq 3 provides reasonably accurate predictions for anthracene solubilities in ternary two alkane + alcohol 14,15 and alkane + two alcohol [16][17][18] solvent mixtures. Such systems exhibit fairly large deviations from solution ideality arising from the self-association of each alcohol cosolvent and, in mixtures containing two alcohol cosolvents, from the formation of heterogeneous hydrogen-bonded chains between dissimilar alcohol molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Equation 1 has been shown to provide very accurate mathematical representations of anthracene, pyrene, and carbazole solubilities in a large number of both complexing and noncomplexing solvent mixtures. [1][2][3] For a ternary solvent system, the mathematical representation takes the form Recent studies have shown that eq 2 provides reasonably accurate predictions for anthracene solubilities in ternary two alkane + alcohol 10,11 and alkane + two alcohol [12][13][14] * To whom correspondence should be addressed. E-mail: acree@unt.edu.…”
Section: Resultsmentioning
confidence: 99%
“…The various S i curve-fit parameters can be evaluated with a least-squares analysis. For a ternary solvent system, the mathematical representation takes the form Recent studies have shown that eq 2 provides reasonably accurate predictions for anthracene solubilities in ternary two alkane + alcohol (Deng and Acree, 1998a;Deng et al, 1999a) and alkane + two alcohol (Deng and Acree, 1998b;Deng et al, 1998 and1999b) solvent mixtures. Such systems exhibit fairly large deviations from solution ideality arising from the self-association of each alcohol cosol-* To whom correspondence should be addressed.…”
Section: Resultsmentioning
confidence: 99%